Reflective Practice: Two Essentials and Three Applications - Danhua Wang (European Teacher Education Network, 2016)
Reflective practice is a special learning process in which past experiences are carefully evaluated in relation to relevant theories. But its distinct qualities are yet to be defined, making it harder to measure its effect. Moreover, the process is prone to human bias since participants are also the subjects of examination. Grounded in epistemology and dual processing theory, this paper argues that a state of doubt and open-minded inquiry should be included as essential features in reflective practice. Three applications, seeking clarity, being open-minded, and uncovering implicit assumptions, are presented to illustrate the central role of the two essential features.